Electrodeposition of Zinc–Copper and Zinc–Tin Films and Free‐Standing Nanowire Arrays from Ionic Liquids. Issue 3 (17th December 2014) - Liu, Zhen; Elbasiony, Amr M.; Zein El Abedin, Sherif; Endres, Frank
Abstract The electrodeposition of Cu–Zn and Zn–Sn films as well as free‐standing nanowires from ionic liquids 1‐ethyl‐3‐methylimidazolium trifluoromethylsulfonate and 1‐butyl‐1‐methylpyrrolidinium trifluoromethylsulfonate is reported. The nanowire arrays were obtained by using polycarbonate membranes. The study includes cyclic voltammetry, chronoamperometry, X‐ray diffraction, and scanning electron microscopy–energy‐dispersive X‐ray analyses. The results show that the morphology and the composition of the electrodeposited Cu–Zn alloys are dependent on the deposition potential. Free‐standing Cu–Zn nanowires with average diameters and lengths of approximately 100 nm and 5 μm, respectively, were prepared. The morphology of Zn–Sn deposits shows coarse Zn particles on a Sn‐rich layer, indicating the formation of Zn/Sn co‐deposits. The XRD results reveal the co‐deposition of Zn–Sn films. Zn–Sn nanowires with average diameters of approximately 100 nm and lengths of 5 μm were synthesized. Free‐standing Zn–Sn nanowires with different lengths and a diameter of approximately 200 nm were also synthesized.